Pengaruh Financial Distress, Ukuran Perusahaan, dan Audit Delay Terhadap Pergantian Auditor - Pratiwi, I Dewa Ayu Adelia; Muliartha RM, Ketut (E-Jurnal Akuntansi, 2019)
Voluntary auditor switching can occur because of problems from both auditor and the company itself. Voluntary auditor switching can arousing suspicion from investor. This study aims to obtain empirical evidence of the effect of financial distress, company size, and audit delay to auditor switching. The population of this research is manufacturing company listed on the Indonesia Stock Exchange in 201 5 -2017 . The method of determining sample using non probability sampling method with purposive sampling technique and obtained 1 68 observations. This study using logistic regression analysis as d ata analysis techniques. The result of analysis shows that financial distress does not infulence auditor switching, company size positively influence auditor switching and audit delay does not influence auditor switching. Keyword:  Pinancial distress, company size, audit delay, auditor switching.